Ayurvedic Management of Chittodvega with Pratimarsha Nasya and Ghrita Pana: A Case Report a Holistic Approach to Generalized Anxiety Disorder (AYUSHDHARA, 2025)
Mental health has become a major concern in today’s increasingly stressful world, impacting individuals and society at large scale. The modern lifestyle usually consists of instability, uncertainty, and constant change which has contributed to widespread psychological strain, leaving many people in the feeling of overwhelmed and disoriented, thereby increasing the risk of developing mental health disorders. Anxiety, a widely recognized mental health disorder, is described in Ayurveda under the category of Manodosha Vikara, specifically identified as Chittodvega. It is considered a type of Manovikara, primarily caused by the aggravation of the Manasika Doshas i.e. Rajas and Tamas and is also regarded as a contributory factor in the pathogenesis of Unmada Roga. In modern psychiatric practice, this condition aligns closely with Generalized Anxiety Disorder (GAD), one of the most commonly encountered mental health disorders in current clinical settings. This case study describes a 32-year-old female patient who presented with chief complaints of persistent overthinking, significant memory decline, restlessness, impaired concentration, and delayed cognitive responses. These symptoms adversely affected her professional and occupational life. In this clinical case, the patient was managed with Pratimarsha Nasya Karma as a local therapeutic procedure, alongside internal administration of Medhya Ghrita as part of Shamana Chikitsa. This combined intervention resulted in significant clinical improvement, with marked reduction in anxiety symptoms, enhanced cognitive clarity, emotional regulation, and improved the sleep cycle.